Consumer Valuation of Alternative Meat Origin Labels. (21st December 2012) - Tonsor, Glynn T.; Schroeder, Ted C.; Lusk, Jayson L.
Abstract: Results from a split‐sample survey of the US population reveal consumers prefer meat products carrying origin information to unlabelled alternatives. Consumers are largely unaware of origin labelling laws and are indifferent to an important aspect of the implementation of current mandatory country of origin information rules in the US. In particular, consumers value meat products labelled 'Product of North America' approximately the same as 'Product of United States'. Despite the similarity of these two labels, they have vastly different implications in terms of trade and segregation costs. Our results suggest that a transition from one label to the other is equally satisfying for the consumer while being less costly for processors and more acceptable to trade partners.